Short-term follow-up of antibiotic-loaded calcium sulfate in treating chronic periprosthetic joint infection during two-stage revision - Sun, Xiao; Tan, Jun; Zhan, Lijuan; Sheng, Mingkui; Tang, Zhongxin; Wu, Lingxiao; Xu, Jianzhong; Ma, Haijun (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundPeriprosthetic joint infection (PJI) is a significant and challenging complication following total knee arthroplasty (TKA). This study aimed to evaluate the efficacy and safety of treating chronic knee PJI with and without antibiotic-loaded calcium sulfate during two-stage revision surgery.MethodsThis retrospective study analyzed 94 patients with TKA infections who underwent two-stage revision between May 2017 and January 2022 at the First Affiliated Hospital of Zhengzhou University. Key outcomes assessed included infection recurrence rates, postoperative range of motion (ROM), Knee Society Score (KSS), Hospital for Special Surgery (HSS) scores, hematological parameters, and complication rates during the follow-up period.ResultsThe demographic characteristics of the two groups showed no significant differences. The infection control rate was significantly higher in the calcium sulfate group (95.7%) compared to the matched control group (80.9%) (P < 0.05). Both groups demonstrated statistically significant improvements in ROM, HSS, and KSS scores compared to preoperative values (P < 0.05). However, intergroup differences in these outcomes were not statistically significant (P > 0.05). Additionally, there was no significant difference in postoperative complication rates between the two groups.ConclusionThe use of antibiotic-loaded calcium sulfate in two-stage revision surgery for chronic knee PJI ensures sustained local antibiotic release at high concentrations, leading to rapid reduction in inflammatory markers, effective infection control, and a low complication rate. This approach is a safe and effective treatment for chronic knee PJI.